The Relationship between Anthropometric Measurements and Modified Mallampati Test in Patients with Chronic Obstructive Pulmonary Disease - Cuglan, Songul; Kose, Evren; Kylyc, Talat; Ogeturk, Murat; Senol, Deniz; Ozbao, Davut; Sapmaz, Hilal Irmak (Wolters Kluwer Medknow Publications, 2022)
Context: The modified Mallampati test (MMT) is one of the most common examination methods to predict possible intubation problems. Aim: The present study aims to investigate the relationship between anthropometric measurements and the MMT in patients with chronic obstructive pulmonary disease (COPD) during the exacerbation period (COPD-E) and stable period (COPD-S). Materials and Methods: The present study included two groups of participants that consisted of 107 healthy individuals in the control group and 107 patients who were diagnosed with COPD (patient group). Two measurements were taken from the patients during the exacerbation and stable periods. The MMT, body mass index (BMI), face height, thyromental distance, and sternomental distance were measured and recorded. Statistical Analysis Used: Data collected were analyzed using the SPSS Statistics for Windows, version 22.0. Results: In the COPD-E period, the MMT score increased, whereas the face height value decreased (P = 0.030). During the COPD-S period, it was found that the higher BMI values were related to higher MMT scores (P = 0.025). The MMT score increased significantly during the COPD-S period, whereas the thyromental distance values decreased (P = 0.034). Conclusion: It is considered that the low face height value in the COPD-E period, the increase in the BMI, and the decrease in the thyromental distance in the COPD-S period could increase the difficult intubation possibility. The results of the present study which may lead to progression in the COPD database would contribute to the clinicians.
Keywords: Anthropometry; COPD; intratracheal; intubation; MMT score